Pengaruh Seo dan Content Marketing terhadap Brand Awareness Melalui Customer Engagement (Studi pada Brand Iqos) - Gozi, Ahmad; Ita Prihatining Wilujeng; Ely Siswanto (Journal of Management and Bussines (JOMB), 2025)
This study aims to examine the impact of Search Engine Optimization (SEO) and content marketing on brand awareness, with customer engagement serving as a mediating variable, focusing on the IQOS brand in Indonesia. SEO and content marketing are two integral components of digital marketing, both designed to enhance brand visibility and foster consumer interaction. Data for this study were collected digitally through questionnaires distributed to active IQOS consumers who participate in the digital space and represent specific demographic segments. The relationships between variables were analyzed in two stages using Structural Equation Modeling with Partial Least Squares (SEM-PLS), both for path analysis and to measure the direct and indirect effects among variables. The findings indicate a positive and significant influence of both SEO and content marketing on customer engagement, which in turn significantly contributes to brand awareness. These results reinforce the importance of optimizing content through SEO to increase market visibility and brand recognition for IQOS. Practically, the findings suggest that SEO and content marketing should be strategically integrated into digital marketing efforts to maximize their effectiveness.   Keywords: Search Engine Optimization (SEO), Content Marketing, Brand Awareness